SOME PARTICULARITIES OF RIVERS’ HIGH FLOW PERIODS FROM SUCEAVA HYDROGRAPHIC BASIN - PORCUŢAN ADRIANA; HÎRLAV C. (Aerul şi Apa: Componente ale Mediului, 2015)
High flow periods represent an important phase in river’s water regime. These periods are represented by high waters and floods. The most important and visible are the floods, because they may have negative effects when they reach water levels that threaten the human life and everything close to it. The analyse of these periods inside Suceava hydrographic basin was made using discharge and level data from the 9 stations inside the basin, 3 on the main river (Brodina 2, Ţibeni and Iţcani), and 6 on the main tributaries (Brodina 2 – Brodina River, Putna – Putna River, Horodnic – Pozen River, Bădeuţi – Suceviţa River, Părhăuţi – Soloneţ River, and Şcheia – Şcheia River).These data were processed using programs such as Microsoft Excel and CAVIS, that gave us a better look over the particularities of high flow periods in this basin. The results bring into attention some rivers that need to be better controlled to prevent further floods and their effects.